Dissemination of the Utilization of Rhizome Plants as Herbal Beverage Products in Braja Gemilang Village - Wandono, Petrus Tri Aji; Talfah, Sajiddah; Khairunnisa; Pasya, Muhammad Zidan; Pratiwi, Almira Alda Eka; Afriliyah, Yessa; Tamara (Research and Social Study Institute, 2024)
The dissemination of the utilization of rhizome plants as the main ingredient in producing health beverages has been conducted in Braja Gemilang Village. This program aims to enhance the community’s understanding and skills in processing rhizomes into herbal drinks with significant health benefits. Rhizome plants such as ginger, turmeric, galangal, and lemongrass were chosen due to their bioactive compounds, which have been proven to positively impact health, such as boosting the immune system, reducing inflammation, and improving digestion. The community service methods applied included dissemination and demonstrations of herbal drink production using rhizome plants. Meanwhile, the writing methodology utilizes experiments and primary data from observations and related literature. The program also introduced processing techniques, ranging from cutting and drying to packaging in practical tea bags. The results of this activity showed high enthusiasm from the community, as evidenced by their active participation during the program. Community members actively asked questions regarding the benefits, preparation methods, and consumption of rhizome-based beverages as an alternative healthy drink and a potential new business opportunity for the residents of Braja Gemilang Village.